PENINGKATAN KESADARAN KESEHATAN REPRODUKSI REMAJA PADA SISWA-SISWI MA AL-MUNAWWAROH MERAUKE - Giovani, Evelin; Floriani, Rosalia; Istiqomah, Nurul; Anggawirya, Arin Mantara; Sijabat, Survey; Purwaningsih, Yuni Ratna; Sahruni, Ade Yuni; Suteki, Mega; Wakerkwa, Dian Agustina Purwanto (Batara Wisnu : Indonesian Journal of Community Services, 2024)
Adolescent reproductive health is very important to study because adolescence is a critical period in physical, mental, and emotional development. A good understanding of reproductive health helps teens make wise and responsible decisions regarding relationships, sexuality, and personal health. Education about reproductive health also plays a key role in dispelling myths and stigma, as well as building a generation that is healthy, knowledgeable, and ready to face life's challenges. This community service aims to raise awareness among MA Al-Munawwaroh Merauke students about the importance of adolescent reproductive health by providing accurate and comprehensive information on its key aspects. This initiative empowers adolescents to take better care of themselves and make informed and responsible decisions regarding their health. The results of this activity successfully increased students' awareness of the importance of adolescent reproductive health. Literacy among MA Al-Munawwaroh Merauke students regarding reproductive health has improved, enabling them to better appreciate and respect themselves and others